Association of MDM2 T309G and p53 Arg72Pro polymorphisms and gastroesophageal reflux disease with survival in esophageal adenocarcinoma. Issue 9 (22nd August 2013) - Renouf, Daniel J; Zhai, Rihong; Sun, Bin; Xu, Wei; Cheung, Winson Y; Heist, Rebecca S; Kulke, Matthew H; Cescon, David; Asomaning, Kofi; Marshall, Ariella L; Li, Su; Christiani, David C; et al.
Abstract: Background and Aim: Although gastroesophageal reflux disease (GERD) is a risk factor for esophageal adenocarcinoma (EAC), some patients develop EAC in the absence of GERD. A putative mechanism of reflux‐induced tumorigenesis involves disruptions in the p53 pathway. We assessed the interaction of GERD and p53 pathway polymorphisms on EAC prognosis. Methods: In a prospective cohort of 358 EAC patients, clinical data (including GERD history and survival) were collected. Germline DNA was genotyped for MDM2 T309G and p53 Arg72Pro . Cox proportional hazards models were used to determine adjusted hazard ratios (AHR) for associations between genotype, GERD, and genotype‐GERD interactions with survival. Results: Compared with other genotypes, MDM2 G/G (median overall survival 21 vs 30 months; P  < 0.001) and p53 Pro/Pro (12 vs 30 months; P  = 0.004) were associated with shorter survival. When analyzed by GERD, MDM2 G/G was associated with shorter survival in patients without GERD (AHR 3.4, 95% CI 2.0–6.0), but not in patients with GERD (AHR 1.1 [0.7–1.8]); the MDM2 ‐GERD interaction was significant ( P  = 0.003). A similar trend was seen for p53 Pro/Pro (AHRs 2.5 without GERD  vs 1.4 with GERD). Combined analysis of at‐risk variants ( MDM2 G or p53 Pro ), revealed each additional at‐risk variant was associated with shorter survival in patients without GERD (AHR 1.6) but not with GERD (AHR 1.0). Conclusions: MDM2 G/G and the combination of MDM2 G and p53 Pro were negative prognostic factors for EAC patients without GERD but not for those with GERD. There may be biological differences between GERD positive and GERD negative EAC.